Analisis Persediaan Bahan Baku Tebu pada Pabrik Gula Pandji PT. Perkebunan Nusantara XI (Persero) Situbondo, Jawa Timur - CHAIRUL BAHTIAR ROBYANTO; MADE ANTARA; RATNA KOMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Analysis of Raw Material In Pabrik Gula Pandji PT. Perkebunan Nusantara XI (Persero) Situbondo, Jawa Timur Raw material is a production cost factor of an industrial manufacture. Lack of raw material may cause production disruption which means manufacture will probably experience profit opportunity loss. This study aims to acknowledge efforts of raw materials supply that Pabrik Gula Pandji PTPN XI (persero) should fulfill. In this study, data had been analyzed in two ways ; Descriptive methods. A research methods that uses analysis in form of narration using logical view to explain numbers in elucidations so that can help in making decisions. (2) Quantitative methods, by several methods, namely: (a) Metode Economical Order Quantity (EOQ); (b) Safety Stock; (c) Reorder Point (ROP); (d) Maximal Inventory (MI); dan (e) metode Total Inventory Cost (TIC). Quantitative methods was done in couple ways ; (a) Metode Economical Order Quantity (EOQ); (b) Safety Stock; (c) Reorder Point (ROP); (d) Maximal Inventory (MI); dan (e) metode Total Inventory Cost (TIC). According to analysis result, total purchase of economical raw materials that manufacture should do is 3.315,62 ton with 71 purchase frequency in one period of production (5 months / year). Minimum stock that PTPN XI (Persero) must own is 1.578,23 ton. While the company had to re-order raw material when raw material stock remains 3.156,47 ton. Maximum stock that should be maintained of the company is 4.893,86 ton. Based on the result of the analysis, total efficiency is Rp 2.903.796,90 /year. Based on above guidelines then can be determined amount of optimal raw material stock that can assure smooth production of white sugar and its cost efficiency. Keywords: analysis of raw material